1995
DOI: 10.3758/bf03197237
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning about curvilinear motion: Using principles or analogy

Abstract: People possess implicit theories about the motion of objects, theories that are often incorrect. When asked to predict the path of an object emerging from a curved tube, for example, people often say that the object will continue to follow a curved path. However, when solving a problem that reminds them of a familiar previous instance, people often reason by analogy to the instance. In this study, we show that a previous instance must be very superficially similar to a problem in order to be used as an analogy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…In what situations might we expect implicit knowledge to be inaccurate? Our data and other studies (e.g., Catrambone et al, 1995;Kaiser et al, 1985) suggest that implicit knowledge might be inaccurate in situations that do not occur very often in everyday life and for which impetus theory and Newtonian physics make different predictions. People rarely see two different masses thrown up with the same initial velocity or balls being shot through curved tubes.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In what situations might we expect implicit knowledge to be inaccurate? Our data and other studies (e.g., Catrambone et al, 1995;Kaiser et al, 1985) suggest that implicit knowledge might be inaccurate in situations that do not occur very often in everyday life and for which impetus theory and Newtonian physics make different predictions. People rarely see two different masses thrown up with the same initial velocity or balls being shot through curved tubes.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, the way in which a problem is presented (in a static diagram or a dynamic animation) or the complexity of the situation may significantly affect task performance (Kaiser, Proffitt, & Anderson, 1985;Kaiser, Proffitt, Whelan, & Hecht, 1992). However, although people make correct predictions in familiar situations, such as water emerging from a curved hose, they are unable to generalize this knowledge to subsequent unfamiliar problems, such as a ball emerging from a curved tube (Catrambone et al, 1995;Kaiser et al, 1986). Catrambone et al concluded that a previous instance must be very superficially similar to a familiar problem to be used as an analogy.…”
Section: Naive Physics Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of the study by Catrambone et al (1995) can also be interpreted as support for simulations. The use of the word "hose" is sufficient to activate stored representations of experiences of using a hose, which can then function as a simulation that generates an answer to the problem.…”
Section: Mental Simulationmentioning
confidence: 76%
“…3 Curved-tube problems from McCloskey et al (1980). Arrows indicate the points at which participants are informed that a ball is inserted into a tube as a hose with water in it (Kaiser, Jonides, & Alexander, 1986a), when the word "hose" is used in the instructions (Catrambone, Jones, Jonides, & Seifert, 1995), and when alterations to the tube or its context serve to activate different stored knowledge (Cooke & Breedin, 1994). The likelihood of drawing curved paths was also found to be lower in a group of six-year-old children (Kaiser, McCloskey, & Proffitt, 1986b); these children tended to say that balls roll straight, and appeared confused by the suggestion of a curved path.…”
Section: The Property Transmission Heuristicmentioning
confidence: 99%